Operationalized Psychodynamic Diagnostic of Adolescents in Light of the New ICD-11 Model of Personality Functioning: Personality Structure, Psychodynamic Conflicts, and Mental Health Problems - Aslı Akın; Kirstin Goth; Inge Seiffge-Krenke; Alexander Obbarius; Sibylle M. Winter; Lea Sarrar (MDPI AG, 2023)
The International Classification of Diseases and Related Health Problems, 11th Revision introduced a fully dimensional approach to personality disorders which conceptionally converges with the long-standing psychodynamic understanding of psychopathology through underlying intra- and interpersonal impairments. In this study, the diagnostic contributions of the two psychodynamic concepts of personality structure and psychodynamic conflicts were investigated through the comparison of self-report data of 189 adolescents with mental health problems and 321 mentally healthy controls. The study results reveal that adolescents with mental health problems show significantly higher impairments in all four domains of personality structure and significantly higher levels of several psychodynamic conflicts. Further, adolescents with different mental health problems significantly differ regarding the impairments in the personality structure domains and several levels of psychodynamic conflicts. While higher structural impairments are shown in adolescents with eating and anxiety disorders, higher levels of the passive self-worth conflict persist in adolescents with depressive disorders, and higher levels of the passive identity conflict are affecting adolescents with eating disorders. The findings suggest that a standardized diagnostic assessment of personality structure and psychodynamic conflicts in adolescent patients could contribute to a deeper understanding of mental health problems and appropriate treatment planning through the detection of underlying intra- and interpersonal impairments.